Deposition History and Paleo-Current Activity on the Southeastern Lomonosov Ridge and its Eurasian Flank Based on Seismic Data - Weigelt, Estella; Jokat, Wilfried; Eisermann, Hannes (Geochemistry, Geophysics, Geosystems, 2020)
A regional seismic survey on the southeastern Lomonosov Ridge (LR) and adjacent basins provides constraints on the coupled evolution of ocean circulations, depositional regime, and tectonic processes. First, Mesozoic strata on the LR, its faulted flanks and the initial Amundsen Basin were covered with syn-rift sediments of Paleocene to early Eocene age. Numerous vertical faults indicate differential compaction of possibly anoxic sediments deposited in the young, still isolated Eurasian Basin. The second stage, as indicated by a prominent high-amplitude-reflector sequence covering the ridge, was a time of widespread changes in deposition conditions, likely controlled by the ongoing subsidence of the LR and gradual opening of the Fram Strait. Episodic incursions of water masses from the North Atlantic probably were the consequences and led to the deposition of thin sedimentary layers of different lithology. The third stage is marked by continuous deposition since the early Miocene (20 Ma). At that time, the ridge no longer posed an obstacle between the Amerasia and Eurasia Basins and pelagic sedimentation was established. Drift bodies, sediment waves, and erosional structures indicate the onset of circulation. Faulting on the ridge slope has led to a series of terraces where sediment drifts have accumulated since the early Miocene. It is suggested that ongoing sagging of the ridge and currents may have shaped the steep sediment free flanks of the terraces. Lastly, a sequence of high-amplitude reflectors marks the transition to the early Pliocene large-scale Northern Hemisphere glaciations.